A case of pityriasis rubra pilaris type IV treated with isotretinoin. - Oliveira, A.; Sanches, M.; Selores, M. (European Journal of Pediatric Dermatology, 2011)
Pityriasis rubra pilaris is a chronic inflammatory dermatosis of unknown etiology and large clinical variability. It has been divided into six categories. Type IV or classical juvenile form occurs in prepubertal children. Here is reported an 11-year-old boy with a 7-day history of circumscribed, salmon plaques, symmetrically distributed on the elbows, knees, sacral region and dorsal aspects of the feet, along with erythema and fine scaling of the face and an orange palmo-plantar keratoderma. The histological examination confirmed the clinical suspicion of pityriasis rubra pilaris type IV and the patient was treated with isotretinoin (0,75mg/kg/day), that led to complete regression of the lesions within 45 days.